Exploring Educational Frontiers: Innovating with Chat-GPT while Upholding Traditional Values - Sain, Zohaib Hassan; Lama, Alma (Journal of Language Development and Linguistics, 2024)
This study investigates the impact of Chat-GPT on education, with a focus on personalized tutoring and academic support. While Chat-GPT offers numerous benefits, there is a risk of misuse for academic dishonesty. Therefore, this research aims to explore how educators can use Chat-GPT to promote academic integrity and encourage critical thinking. To accomplish this, the study utilizes both quantitative and qualitative approaches, beginning with a literature review. Interviews with instructors, students, and industry professionals provide different perspectives and reveal practical challenges. Additionally, performance indicators are used to compare Chat-GPT with traditional teaching methods. Initial tests demonstrate potential, but ongoing development requires educators to balance the advantages and risks, address concerns about academic honesty, and foster critical thinking skills in students.